Pseudo-ring tests resolution for dynamic single faults in word-oriented memory - S. S. Gritcov; G. F. Sorokin; T. V. Shestacova (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
This paper presents single dynamic faults and methods for their detection. Such dynamic faults as dRDF, dDRDF and dIRF are considered in detail. Also, pseudo-ring testing and the principles of single dynamic faults detecting by pseudo-ring tests are considered. The paper presents the resolution determination results for pseudo-ring tests in relation to these faults in the word-oriented memory. Also, a comparative analysis of the pseudo-ring tests with known March tests is done. The results show that pseudo-ring tests with an algorithmic complexity of (30-60)N, where N is the number of all memory cells, can cover from 75 to 100% of all single dynamic faults. This advantage allows using pseudo-ring tests as an alternative to existing classical and March tests.